2014
DOI: 10.1071/rd13305
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biomicroscopy: a non-invasive approach for in vivo evaluation of oocytes and small antral follicles in mammals

Abstract: The use of ultrasonography has changed our understanding of the ovarian function in live animals. However, most of the studies that have used ultrasonography to image the ovary have provided data only of structures >1mm in diameter. The recent availability of high-resolution ultrasound technology with high-frequency transducers (25-70 MHz), offers the potential to examine the developmental dynamics of small antral follicles and the cumulus-oocyte complex (COC) in vivo. In this review we provide data from a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The objective of the present study was to validate the use of UBM histochemical analyses. 1,2,27 UBM has facilitated several fields of basic research and clinical applications, including developmental biology, 28 female reproductive biology, [18][19][20][21][22] cardiology, [29][30][31] neurology, 32 oncology, 13,17,33,34 embryology, 14 and ophthalmology. 10,35,36 In a recent feasibility study, we showed that UBM has the potential to be used as a predictive tool for the development of testis tissue grafts and cell implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of the present study was to validate the use of UBM histochemical analyses. 1,2,27 UBM has facilitated several fields of basic research and clinical applications, including developmental biology, 28 female reproductive biology, [18][19][20][21][22] cardiology, [29][30][31] neurology, 32 oncology, 13,17,33,34 embryology, 14 and ophthalmology. 10,35,36 In a recent feasibility study, we showed that UBM has the potential to be used as a predictive tool for the development of testis tissue grafts and cell implants.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Because of its low cost, high speed, accuracy, and non-invasiveness, UBM has been widely used in imaging of laboratory animals, especially to investigate pathogenesis of diseases and embryonic development of mice. [13][14][15][16][17] This technology has been successfully used in reproductive sciences to visualize the ovarian follicular development and cumulus-oocyte complexes in laboratory animals 18,19 as well as in farm animals 20,21 and humans. 21,22 UBM has also been utilized in three-dimensional (3-D) measurements of melanomas in mice where the UBM-measured dimensions were shown to be in excellent agreement with those measured using the caliper volume of tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noticing that putative COCs appearing as protrusion into the fluid-filled lumen can only be detected in less than 25% of the ovarian follicles by ultrasound biomicroscopy. SPIM far outperforms the ultrasound techniques in terms of the spatial resolution14, and is thus more suitable for small follicle detection.…”
Section: Resultsmentioning
confidence: 97%